1976
DOI: 10.1902/jop.1976.47.11.621
|View full text |Cite
|
Sign up to set email alerts
|

Host Response in Chronic Periodontal Disease: V. The Dental and Periodontal Status of Mink and Mice Affected by Chediak‐Higashi Syndrome

Abstract: IN BOTH HUMANS and animals, the accumulation of microbial plaque leads to the infiltration of large numbers of neutrophils within the marginal gingival tissues at a time prior to the appearance of lymphoid cells. 16 The appearance of these cells is accompanied by loss of a large portion of the collagen fibers immediately subjacent to the junctional epithelium. 4 6 Neutrophils have the capacity to ingest and kill microorganisms and they may be predominantly protective, although it has been suggested that they m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In the lower jaw, the amount of attached gingiva is narrow in the incisors and premolars. Around the molars, attached gingiva appeared to be comparable to that observed in the upper jaw [106]. In CSH-affected minks, periodontal disease occurs rapidly with a high hemorrhagic inflammatory response in the marginal gingiva.…”
Section: The Different Animal Models In Periodontologymentioning
confidence: 99%
“…In the lower jaw, the amount of attached gingiva is narrow in the incisors and premolars. Around the molars, attached gingiva appeared to be comparable to that observed in the upper jaw [106]. In CSH-affected minks, periodontal disease occurs rapidly with a high hemorrhagic inflammatory response in the marginal gingiva.…”
Section: The Different Animal Models In Periodontologymentioning
confidence: 99%
“…Those affected are very susceptible to bacterial infections due to alterations in the functional capacity of the polymorphonuclear leukocyte. Humans (59) and other animals (105) with Chediak–Higashi syndrome exhibit generalized, severe gingivitis and extensive loss of alveolar bone and premature loss of teeth (168). The polymorphonuclear leukocyte chemotactic and bactericidal functions are thought to be abnormal in these patients.…”
Section: Evidence For the Role Of Genetic Variants In Periodontitismentioning
confidence: 99%
“…Polymorphonuelear neutrophils are an essential part of host defense against invading bacteria (1). Several studies have shown that periodontal diseases in man (2)(3)(4)(5) and in animal (6) arc associated with defective neutrophil function, providing support lor the concept that neutrophils are protective against pathogenic oral bacteria. In addition, several studies have shown that crcvicular neutrophils function better in vitro when they are recovered from healthy compared with diseased gingival pockets (7).…”
mentioning
confidence: 90%